Rancang Bangun Aplikasi e-Commerce Dropship Berbasis Web - Alexander Waworuntu (Faculty of Engineering and Informatics, Universitas Multimedia Nusantara, 2020)
Inabay is a small business that provides various types of products from stationery to food supplements which are distributed through dropship mechanism. The transaction process with drop shippers are still carried out conventionally with a large number of drop shippers/resellers, causes resellers unable to monitor product stock in real-time. Therefore, Inabay develops a web-based e-commerce application that can be used by resellers to make purchases of goods and monitor the movement of stock quantities. The application development process adapts the Rapid Application Development method and uses the PHP programming language with Laravel framework and MariaDB database. User acceptance of the application is evaluated using the Technology Acceptance Model with the results of 88% perceived ease of use and 96% perceived usefulness.